(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the sales promotion activities of Tingketbelle Silk Sleepwear's online fashion shop. Based on the results of this study, this paper will assist the Tingketbelle Silk Sleepwear online fashion shop in understanding the sales promotion activities. This study utilized a descriptive research method to gather data from 50 respondents. A purposive sampling technique was employed to select respondents. The study presents data on the demographic profile, sales promotion activities of Tingketbelle Silk Sleepwear, sales promotional activities affecting online sales, problems encountered by the respondents in sales promotional activities of Tingketbelle Silk Sleepwear, and the improvement plan that can be proposed by the researchers. Statistical tools used were frequency, percentage, and weighted mean. Based on the data, the majority of respondents were 21-30 years old and had the highest frequency and percentage of 62% in the respondents' profiles in terms of age. Females got the highest frequency and percentage of 82% in respondents' profiles in terms of gender. Customers were satisfied with the sales promotion activities of Tingketbelle Silk Sleepwear in terms of contests and bundles, and they were very satisfied in terms of raffles. The sales promotional activities affect online sales in terms of quality, affordability, and mode of payment, as respondents were very satisfied. With 35.71%, competition in giveaways caused the highest percentage of problems encountered by the respondents of the Tingketbelle Silk Sleepwear online shop. Based on the findings of the study, it is recommended to set a limited time for bidding to be fair with the customers who were waiting and wanted to avail of the products. Reduce the minimum purchase amount to be part of the contest. More customers will buy more products to join the contest. Lower the required amount to attract more customers to buy the products. Always update the customers for giveaway promotions.